Reforming State-Owned Enterprises in Asia challenges and solutions - Farhad, Hesary (Springer, 2021)
This book analyzes state-owned enterprises (SOEs), which are still significant players in many Asian economies. They provide essential public services, build and operate key infrastructure, and are often reservoirs of public employment. Their characteristics and inherent competitive advantages as publicly owned enterprises allow them to play these critical roles. Their weaknesses in governance and inefficiencies in incentive structures, however, also often lead to poor performance.
Keywords: Asia